The Climax-Decline Pattern in the Book of Kings - Klein, Neriah (Zeitschrift für die alttestamentliche Wissenschaft, 2024)
The Book of Kings is the main source for reconstructing the chronology of the monarchic period in Israel, but it contains many contradictions and raises difficulties that make the reconstruction disputed to this day. The prevailing approach tends to attribute historical credibility to the biblical data, while few have suggested that some of the numbers have been deliberately manipulated to create symbolic or meaningful schemas. The purpose of the present study is to reinforce the artificiality of these numbers by presenting two cases of a »climax-decline pattern« at key points in the Book of Kings’ chronology, in which a king with the longest reign in the history of a kingdom is followed by a period of deterioration towards disaster over the same duration. If these regnal years have been reworked to incorporate them into the book’s literary design, then they may mislead the historian who wishes to use them to reconstruct a relative or absolute chronology.